Perancangan Pasar Induk Di Linggajaya Tasikmalaya Dengan Pendekatan Arsitektur Vernakular - Mubarok, Fuji Farid; Endangsih, Tri; Subagya, Karya (MAESTRO, 2024)
The level of development in the city of Tasikmalaya is quite high in the Priangan region, contributing to the economic growth of the city. Given the fact that the non-agricultural sector that absorbs the most labor is the trade sector, the Tasikmalaya Local Government at Level II provides a Public Market aimed at accommodating large-scale trading activities. Cikurubuk Market serves as both a wholesale and retail market, expected to meet the needs of the people of Tasikmalaya, not only in terms of acquiring goods but also in terms of market facilities, circulation comfort, and accessibility convenience. Because Cikurubuk Market not only involves transactional activities but also transportation services passing through the market, a rearrangement is needed to meet expectations, providing space based on characteristics. Trading activities are grouped into wholesale trade, official retail trade, and unofficial retail trade. With the grouping of these trading activities, visitors will find it easier to reach their destinations. The grouping of trade and circulation can direct visitors to their destinations easily and smoothly, avoiding congestion and concentration of activities within the market, ensuring that the processes of each user do not interfere with each other.